2011
DOI: 10.1007/s12015-011-9247-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Guiding Migration of Human Induced Pluripotent Stem Cells

Abstract: A major road-block in stem cell therapy is the poor homing and integration of transplanted stem cells with the targeted host tissue. Human induced pluripotent stem (hiPS) cells are considered an excellent alternative to embryonic stem (ES) cells and we tested the feasibility of using small, physiological electric fields (EFs) to guide hiPS cells to their target. Applied EFs stimulated and guided migration of cultured hiPS cells toward the anode, with a stimulation threshold of <30 mV/mm; in three-dimensional (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 35 publications
1
52
1
Order By: Relevance
“…Here, adult human bone marrow-derived MSCs showed strong anodal electrotaxis in physiological EFs, and this migration response increased with increasing EF strength between 25-300 mV/mm. Human induced pluripotent stem cell (hiPS) also show anodal electrotaxis in physiological EFs (Zhang et al, 2011). However, mouse adipose-derived stromal cells (mASC) migrated towards the cathode in response to EFs (Hammerick et al, 2010).…”
Section: Z Zhao Et Al Electrotaxis Of Bone Marrow Mesenchymal Stem Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, adult human bone marrow-derived MSCs showed strong anodal electrotaxis in physiological EFs, and this migration response increased with increasing EF strength between 25-300 mV/mm. Human induced pluripotent stem cell (hiPS) also show anodal electrotaxis in physiological EFs (Zhang et al, 2011). However, mouse adipose-derived stromal cells (mASC) migrated towards the cathode in response to EFs (Hammerick et al, 2010).…”
Section: Z Zhao Et Al Electrotaxis Of Bone Marrow Mesenchymal Stem Cmentioning
confidence: 99%
“…There are many advantages to using low voltages for EF stimulation. The most important ones for developing a practical technique of EF application is that this will signifi cantly prevent electro-chemical product generation (from electrodes), the generation of heat, and effects on other cell types in 3D tissues Zhang et al, 2011). This will also allow more prolonged application in clinical practice.…”
Section: Z Zhao Et Al Electrotaxis Of Bone Marrow Mesenchymal Stem Cmentioning
confidence: 99%
“…From early research, electrotaxis has been known to play a profound role in embryonic development, neurogenesis, and wound healing. 1,2 Many different cell types and organisms show electrotactic response to dcEF, including neural stem cell, 3 induced pluripotent stem cells, 4 mesenchymal stem cells, 5,6 fibroblasts, [7][8][9] keratinocytes, 10,11 neurons, 2 and C. elegans. 12,13 The physiological dcEF with strength of tens to hundreds of mV per mm (mVÁmm À1 ) originates from the difference in transepithelial potential (TEP), which is supposedly formed by the differential distribution of ion channels on polarized epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported the use of the 3D Matrigel for studying electrotaxis of human induced pluripotent stem (hiPS) cells. 14 The cells were mixed with Matrigel followed by transference to the electrotactic chamber. The study showed that dcEF can stimulate and direct hiPS cell migration in 3D.…”
Section: Assaysmentioning
confidence: 99%